Analisis Strategi Customer Relationship Management (CRM) Terhadap Efektivitas Perusahaan Go-Jek Di Era Era Digital Masa Kini - Joy Stevani Simangunsong; Yoga Saputra Manihuruk; Rizki Sitanggang; Lenti Susana Saragih (Pusat Riset dan Inovasi Nasional, 2023)
This research uses a library research method with a library research approach. This research was designed to identify the strategies implemented by Go-Jek, the impact of implementing CRM, obstacles in implementing CRM, and solutions to overcome these obstacles. Gojek CRM is a company that has many enthusiasts and customers. This land transportation company operating in the service sector utilizes developments in information technology to market the service products it produces. CRM allows businesses to better understand what their customers need and want, preventing them from switching to other companies in today's digital era.